Effectiveness of the Ombudsman of the Republic of Indonesia Representative of West Nusa Tenggara Province in Supervising Tourism Villages - Kafrawi, Rachman Maulana; Khairul Umam; Rahmadani, Rahmadani; Muh. Alfian Fallahiyan (JATISWARA, 2024)
The Ombudsman of the Republic of Indonesia or later called the Ombudsman is an independent state institution which has the authority to supervise the process of providing public services carried out by State and Government administrators including State-Owned Enterprises (BUMN), Regional-Owned Enterprises (BUMD), State-Owned and Private Legal Entities which have been given the task of providing certain public services. The research discusses the effectiveness of the Indonesian Ombudsman Representative of West Nusa Tenggara Province in Supervising Tourism Villages. This research is based on the large number of public reports submitted to the Ombudsman regarding alleged violations that occurred in the administration of the Tourism Village. For this reason, supervision by the Ombudsman is needed to manage public complaints and prevent repeated maladministration in the administration of Tourism Villages. This research is socio-legal research with a statutory approach, a conceptual approach and a sociological approach. Research results In supervising public services, apart from receiving reports from the public, the Ombudsman can also carry out on his own initiative through a systemic review, the results of which can be in the form of recommendations/suggestions. The Ombudsman's supervision in supervising the implementation of tourist villages can be said to be effective and running well in accordance with the indicators.